Multi-phase structures of boron-doped copper tin sulfide nanoparticles synthesized by chemical bath deposition for optoelectronic devices - Jariya Rakspun (2018)
© 2017 Elsevier Ltd We investigated the influence of boron doping on the structural, optical, and electrical properties of copper tin sulfide (CTS) nanoparticles coated on a WO3surface and synthesized using chemical bath deposition. Boron doping at concentrations of 0.5, 1.0, 1.5, and 2.0 wt% was investigated. The X-ray diffraction pattern of CTS showed the presence of monoclinic Cu2Sn3S7, cubic Cu2SnS3and orthorhombic Cu4SnS4. Boron doping influenced the preferred orientation of the nanoparticles for all phase structures and produced a lattice strain effect and changes in the dislocation density. Increasing the concentration of boron in CTS from 0.5 wt% to 2.0 wt% reduced the band gap for all phases of CTS from 1.46 to 1.29 eV and reduced the optical transmittance. Optical constants, such as the refractive index, extinction coefficient, and dissipation factor, were also obtained for B-doped CTS. The dispersion behavior of the refractive index was investigated in terms of a single oscillator model and the physical parameters were determined. Fourier transform infrared spectroscopy confirmed the successful synthesis of CTS nanoparticles. Cyclic voltammetry indicated that optimum boron doping (<1.5 wt% for all phases) resulted in desirable p-n junction behavior for optoelectronic applications.